Taxonomy of digital signage message execution and media placement considerations - E M Xaba; AT Roux; GAP Drotsky (The Retail and Marketing Review, 2020)
Digital signage is a commercial promising field in marketing. Yet, it is a little researched topic, with an incomplete understanding of the factors to consider when planning digital signage message executions or media placements. There is no systematic, cohesive foundation to describe and study the features of this promising contemporary digital platform. This paper addresses an academic-practitioner divide by developing an orderly categorisation of digital signage message execution and media placement considerations and research. It offers a well-ordered conceptualisation of digital signage types and guidelines for selecting content types, formats, display quality and technical interactive designs. The resulting taxonomy is of relevance to retailers and marketers aiming to optimise utilitarian or hedonic value. Some guidance for prospect research is provided, particularly assessing the varies opportunities offered by different digital signage content types; designing experiments compare the effectiveness of digital display quality, sizes, placement and designs at different locations. The possible obstacles of interactive digital signage also deserve future research.